Vloga tržnega komuniciranja v podjetju - Kobold, Sara (Management, 2014)
Marketing communication is an integral part of the famous 4-\kratica{P}. It plays an important role in the company, as it helps to increase company's visibility and strengthen its brand. Marketing communication is achieving its objectives in communicating with customers and consumers using its marketing communication tools. If a company wants to be ahead of the competition, and have a good look in costumers' ayes, marketing communication is most crucial. In this paper we analyze the case of marketing communication company Lumar. The results obtained argue that the company is well known, where we recognize especially the electronic media as most important tool of marketing communication. However, we noticed that the brand recognized more regionally -- especially in Styria and Carinthia, despite the fact that the company is well known and active in all regions in Slovenia and abroad (Italy, Germany, Austria).
Keywords: blagovne znamke; podjetja; prodaja; strategija; trženje; tržno komuniciranje